1976
DOI: 10.1021/je60068a027
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of xenon in liquid sodium

Abstract: The solubility of xenon In liquid sodium was measured as a function of pressure (2-8 atm) and temperature (350-600°C). Henry's law was obeyed with the value of the Henry's law constant, KH = %,/P, ranging from 1.38 X atm-' at 600°C, where be and Pare the atom fraction and the partial pressure of xenon, respectively. The temperature dependence of solubility may be represented by loglo = (0.663 f 0.01) -(4500 f 73) T1, where X Is the Oslwald coefficient (the volume of xenon dissolved per unit volume of sodium at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…It may be that we were unable to obtain a horizontal asymptote in plots of p͞X against X for the vapor pressures of chloroform-acetone solutions because there were not data at sufficiently low values of X to demonstrate the validity of Henry's law. Certainly, many examples exist in the literature in which the authors claim that they have demonstrated that Henry's law is followed in the system studied (2,15,16), usually by plotting pressure against mole fraction and seeing a straight line. We have seen that Giacobbe (2) correctly concluded that solutions of CO 2 in acetone follow Henry's law at pressures below 10 atmospheres.…”
Section: Is Henry's Law Only a Limiting Law For Binary Solutions?mentioning
confidence: 99%
“…It may be that we were unable to obtain a horizontal asymptote in plots of p͞X against X for the vapor pressures of chloroform-acetone solutions because there were not data at sufficiently low values of X to demonstrate the validity of Henry's law. Certainly, many examples exist in the literature in which the authors claim that they have demonstrated that Henry's law is followed in the system studied (2,15,16), usually by plotting pressure against mole fraction and seeing a straight line. We have seen that Giacobbe (2) correctly concluded that solutions of CO 2 in acetone follow Henry's law at pressures below 10 atmospheres.…”
Section: Is Henry's Law Only a Limiting Law For Binary Solutions?mentioning
confidence: 99%